Efektivitas Metode Diskusi Dalam Pembelajaran Kitab Kuning Terhadap Kepribadian Santri Di Pondok Pesantren - Khusnan, Ach (FATAWA: Jurnal Pendidikan Agama Islam, 2020)
Several centuries ago when humans were in the age of ignorance, Allah SWT sent His messenger by lowering the holy book to him, a book containing the guidelines for life that guide humans to the path of peace, which contains warnings and good news, in the first revelation clearly. Al-Qur'an explains with the word "iqro '(read)" the verse indicates that Islam highly upholds the value of education. That means that humans are basically teachable and teachable creatures. Because the object of the word iqro 'is a human being as a whole. This is the most fundamental right of the profile and description of human beings. with education, human existence as kholifah of Allah SWT is given the responsibility to care for nature and its contents. the UUSPN Law on the National Education System No. 20 of 2003 it is stated as follows:"Education functions to develop abilities and shape the character of a dignified national civilization in order to educate the nation's life, aims to develop the potential of students to become human beings who believe and devote to an almighty god, have noble character, are healthy, knowledgeable, competent, creative, be independent and become a democratic and responsible citizen.â€ To bring the community, especially the younger generation, to be able to play a role as expected, a forum for the educational process is needed, in which the educational process takes place simultaneously with the culture process. A person through the process of life in a family, he continues his development through the help of others, both parents and education. This is so that children gain experience, knowledge, and ability to act in accordance with prevailing cultural norms and values. More knowledge is obtained from educational institutions that foster children to become qualified humans or have higher education quality. For this reason, the application of education should be carried out by a forum that supports their learning with a conducive situation and adequate facilities as well as a good learning climate, among these are Islamic boarding schools.